DETERMINAN PERMINTAAN PERUMAHAN DI KOTA MATARAM - Salmah, Emi; Harsono, Iwan; Ismiwati, Baiq; Wijimulawiani, Baiq Saripta; Handayani, Tuti (Elastisitas : Jurnal Ekonomi Pembangunan, 2024)
A place to live or a house is a necessary necessity in living human daily life. Mataram City is the capital of West Nusa Tenggara (NTB) Province and is one of the centers of economic growth, with a high population growth rate compared to 10 other districts/cities in NTB. This population growth causes the demand for housing/own houses or property rights to be very high, but on the other hand, land is getting narrower and more expensive, resulting in house prices becoming expensive and this has a big impact on people who are less fortunate in terms of their income. To meet the demand for housing from the community, we encourage developers to build housing with various types/models that are tailored to the income and desires of the community. The aim of the research is to analyze the influence of population, per capita income and inflation on housing demand in Mataram City. This research uses secondary data obtained from BPS Mataram City, BPS NTB Province, NTB Housing Statistics and other data sources relevant to this research. The data were analyzed using a multiple linear regression model with panel data and using the Eviews 12 calculation tool. The results of the study showed that the results of the multiple linear regression using the OLS method were found to have two variables that had a significant effect, namely the population and GRDP variables, while the inflation variable had an effect not significant.